Recasts and output-only prompts, individual learner factors and short-term EFL learning. (August 2018) - Li, Huifang (Lydia)
Abstract: This study investigated the effects of recasts and output-only prompts (i.e., clarification requests, elicitations, and repetitions) on short-term EFL learning regarding three learner factors (i.e., learner level, language anxiety, and orientation to correction). Ninety Mandarin-speaking learners at a Chinese university were randomly assigned to one of two experimental groups or a control group. While all the learners completed the pre-/post-tests and had their weekly English lessons as usual, only the learners in the experimental groups received feedback treatment in three extracurricular lessons. Learner level was differentiated according to the pre-test performances, and data on language anxiety and orientation to correction were collected through a questionnaire at the end of the treatment. Results show that all the learners in the recast group benefited from the treatment regardless of their trait for each learner factor, whereas the learners in the prompt group who benefited from the treatment lessons scored low in the pre-test, had a low level of language anxiety, or showed a high level of orientation to correction. These results suggest that recasts can be more advantageous for learning than prompts in certain classroom contexts, for example, the focused context of the present study.